2006
DOI: 10.1039/b605345a
|View full text |Cite
|
Sign up to set email alerts
|

o-Phenylene-bridged Cp/sulfonamido titanium complexes for ethylene/1-octene copolymerization

Abstract: The Suzuki-coupling reaction of 2-(dihydroxyboryl)-3,4-dimethyl-2-cyclopenten-1-one and 2-(dihydroxyboryl)-3-methyl-2-cyclopenten-1-one with 2-bromoaniline derivatives affords cyclopentenone compounds from which cyclopentadiene compounds, 4,6-R'(2)-2-(2,5-Me2C5H3)C6H2NH2 and 4,6-R'(2)-2-(2,3,5-Me3C5H2)C6H2NH2 are prepared. After sulfonation of the -NH2 group with p-TsCl, metallation is carried out by successive addition of Ti(NMe2)4 and Me2SiCl2 affording o-phenylene-bridged Cp/sulfonamido titanium dichloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Lee and coworkers [ 79,80 ] systematically studied the effects of the substituents in the bridged phenyl group and the cyclopentadienyl group on the polymerization activity, polymer molecular weight, and comonomer insertion ability by changing the catalyst ligand structure. The results showed that the highest activity was achieved when the trimethyl group was substituted on the cyclopentene ring.…”
Section: Metallocene Catalyst For Ethylene/α‐olefin Solution Copolyme...mentioning
confidence: 99%
“…Lee and coworkers [ 79,80 ] systematically studied the effects of the substituents in the bridged phenyl group and the cyclopentadienyl group on the polymerization activity, polymer molecular weight, and comonomer insertion ability by changing the catalyst ligand structure. The results showed that the highest activity was achieved when the trimethyl group was substituted on the cyclopentene ring.…”
Section: Metallocene Catalyst For Ethylene/α‐olefin Solution Copolyme...mentioning
confidence: 99%